Food regulation and trade: toward a safe and open global system - Josling, Timonthy; Roberts, Donna H.; Orden, David (Institute for International Economics, 2004)
Guarding the safety of a nation's food supply and providing standards and information to guide consumers' food choices are the joint responsibilities of governments and the private sector. But differences in the way countries fulfill these obligations can lead to trade conflicts in sectors ranging from beef to Bt corn. Regulatory protection of domestic producers sparked most trade disputes in the past, but as food technologies advance and as products become more differentiated, consumers seek additional regulations from their governments, thus increasing the scope for conflict. This book examines the current state of agricultural and food regulations as they affect trade. The authors discuss the efficacy and compatibility of countries' food regulations and analyze the tensions that have emerged from increased regulation based on production processes as well as final content. They assess the need for strengthening the rules of the WTO and other international institutions charged with oversight of national policies and recommend other ways that regulation can enhance the benefits of an open food system.